Foreign Aid and Economic Growth: A Case of South Asian Countries - Devkota, Khim Lal (Economic Journal of Nepal, 2008)
Foreign aid for any developing country is inseparable entity from its economic growth. Thus the relationship between economic growth and foreign aid is investigated from a panel data set of developing south Asian countries over the period 1980-2006. have estimated the responsiveness of aid to these countries' economic, demographic and political needs and use fixed effects to control unobserved country specific effects of donors. 1 found that per capita income and foreign aid have been negatively related. while aid has been positively related to population and external debt. The negative coefficients on per capita GDP suggests that Donor aid favors south Asian countries in allocating aid, supporting the hypothesis that recipient needs do have an effect on foreign aid allocation. Also, the hypothesis that countries with a higher score receive more foreign aid as a reward for their democratic orientation is tested and, quite surprisingly rejected.Key words: Foreign aid; Economic growth; South Asian countriesEconomic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 31, No. 4 October-December 2008, Issue No. 124Page: 246-267Uploaded date: 5 July 2011